Burden of pneumococcal disease due to serotypes covered by the 13-valent and new higher-valent pneumococcal conjugate vaccines in the United States. Issue 33 (5th August 2022) - Huang, Liping; Wasserman, Matt; Grant, Lindsay; Farkouh, Raymond; Snow, Vincenza; Arguedas, Adriano; Chilson, Erica; Sato, Reiko; Perdrizet, Johnna
Highlights: Pneumococcal conjugate vaccines (PCVs) greatly reduced pneumococcal disease burden. Reductions have been shown in invasive and non-invasive pneumococcal disease. Sizeable clinical and economic disease burden remains despite longstanding PCV use. Serotypes covered in higher-valent PCVs are associated with greater disease burden. Higher direct annual costs are associated with serotypes in PCV20. Abstract: The addition of pneumococcal conjugate vaccines (PCVs) to the United States (US) national immunization program led to significant reductions in incidence, mortality, and associated sequelae caused by pneumococcal disease (PD) in children and adults through direct and indirect protection. However, there remains clinical and economic burden due to PD caused by serotypes not included in the current 13-valent PCV (PCV13) formulation. To address this unmet need, 15-valent PCV (PCV15) and 20-valent PCV (PCV20), containing additional serotypes to PCV13, were recently approved in the US for adults and are anticipated for pediatrics in the near future. The study objective was to estimate the annual number of cases, deaths, and economic burden of PD due to serotypes included in PCV13, PCV15, and PCV20 for both US pediatric and adult populations. An Excel-based model was developed to calculate clinical and economic outcomes using published age-group specific serotype coverage; incidence of invasive PD, community-acquired pneumonia, and acute otitis media; case fatality rates; and disease-related costs. The results showed that across all age groups, the estimated annual PD cases and associated deaths covered by PCV13 serotypes were 914, 199 and 4320, respectively. Compared with PCV13 serotypes, the additional 2 and 7 serotypes covered by PCV15 and PCV20 were attributed with 550, 475 and 991, 220 annual PD cases, as well as 1425 and 3226 annual deaths, respectively. This clinical burden translates into considerable economic costs ranging from $903 to $1, 928 million USD that could be potentially addressed by PCV15 and PCV20. The additional serotypes included in PCV20 contribute substantially to the clinical and economic PD burden in the US pediatric and adult populations. Despite the success of the PCV13 pediatric national immunization program and increased adult uptake of PCV13 and 23-valent polysaccharide vaccine, broader PCV serotype coverage is needed across all ages to further reduce pneumococcal disease burden.